A numerical study of liquid film dynamics in multi-nozzle spray cooling of downward-facing surface. (April 2023) - Fang, Di; Xiang, Yan; Deng, Yucheng; Ma, Weimin
Highlights: 3D Eulerian-Lagrangian model for upward-spray case is developed. Film dynamics in spray impingement with 6 nozzles are investigated numerically. Film thickness and velocity on a downward plate are computed. Effects due to inclination, nozzle distance and nozzle array layout are studied. Abstract: In a consideration of spray cooling as the potential cooling mechanism for the in-vessel melt retention (IVR) strategy of nuclear reactors because of its superior heat removal efficiency, the SPAYCOR experiment has been conducted at KTH to investigate the spray cooling capacity of multiple nozzles applied to a downward-facing heated surface. In the present study, the dynamics of liquid film on the downward-facing surface resulting from the multi-nozzle spray are numerically simulated by using a coupled Eulerian-Lagrangian method implemented in the OpenFOAM platform. Prior to simulation of the SPAYCOR experiment, the numerical approach is used to calculate two theoretical setups which have known analytical solutions, with the objective to validate the models in predicting liquid film dynamics either in spray or on an inclined surface. In the simulation of the SPAYCOR experiment, the predicted film morphology shows a good agreement with the experimental observation. What's more, the influential factors, including the inclination of the downward-facing heater surface, the nozzle-to-surface distance as well as the nozzle-array layout, are also investigated numerically in the present study. The simulation results show that a decreasing nozzle-to-surface distance does not only lead to a thicker liquid film and a lower velocity in the vicinity of each spray coverage, but also increases non-uniformity of the liquid film. The nozzles-array layout has little influence on the average liquid film thickness and velocity, but significantly affects the film morphology.